The global change? International Ports Congress 1999 ; proceedings of the international congress organized by the Institution of Civil Engineers and held in Southampton, UK, on 14-15 June 1999 - Carmichael, John (Thomas Telford, 2000)
In this work particular attention is given to the most recent developments in design and construction methods and how these must be economically integrated with operational requirements and environmental considerations.